Fungi associated with the blighted leaf symptoms of Hevea brasiliensis in Malaysia - Syed Sagaff, Sharifah Aliya; Syd Ali, Nusaibah (Wiley-Blackwell, 2021)
This article describes the fungi isolated from the blighted leaf of rubber (Hevea brasiliensis) tree in Malaysia. Previously, Neofusicoccum ribis (Family Botryosphaeriaceae) was reported as the causal agent of rubber leaf blight in Malaysia. To date, there are limited studies on this particular disease in Malaysia and worldwide. The current study was carried out on rubber leaves displaying leaf blight symptoms caused by N. ribis from different locations to discover the fungi that reside in the blighted leaves. Rubber leaf samples with blight symptoms were collected from two different locations in Malaysia. The fungal isolates were isolated following the agar plate method and subjected to cultural and morphological characterization. Based on the cultural and morphological characterization, eight fungal isolates were further subjected to molecular identification. Five fungal isolates namely SBI, SB2, SB3, SB6 and SPKT1 were identified as N. ribis, one fungus (SB4) as Diaporthe drenthii, and another two fungi namely SB5 and SPKT2 were identified as Lasiodiplodia pseudotheobromae. Based on the morphological and molecular identification, all the N. ribis isolates demonstrated similar characteristics of the rubber leaf blight pathogen as documented in a previous study.